PERCEPTION OF THE FEMALE ROLE IN SAUDI ARABIAN SOCIETY. - DE JONG, OLGA ACOSTA. (The University of Arizona., 1986)
The present investigation examines the roles of women in the rapidly changing society of the Kingdom of Saudi Arabia and attempts to quantify and optimize their role as active contributors to the development of the country. The study starts out with a review of earlier work on women's roles in the Kingdom and then throws a more recent light on the subject by analyzing the current writings and comments in the popular press. Those findings are supplemented by direct interviews with samples from various segments of the Saudi population; answers are compared with similar inquiries by earlier researchers as well as with opinions expressed in the media. Since these results are primarily of a subjective nature the study then proceeds to quantify the role Saudi women play as educated and productive contributors to the development of the Kingdom. From published data a numerical framework is described, which is followed by a modelling effort, using the goal programming algorithm, aimed at optimizing the use of the female labor force in Saudi Arabia. Under present policies and as a result of social and traditional attitudes many of the labor market positions are now available for occupancy by Saudi women but they are filled by female or male imported labor. The impacts of selected changes in current manpower policies are analyzed.